How Soluble Fms-Like Tyrosine Kinase 1 Could Contribute to Blood-Brain Barrier Dysfunction in Preeclampsia? - Torres-Vergara, Pablo; Rivera, Robin; Escudero, Carlos (Frontiers in Physiology, 2022)
Preeclampsia is a pregnancy-related syndrome that courses with severe cerebrovascular complications if not properly managed. Findings from pre-clinical and clinical studies have proposed that the imbalance between pro- and anti- angiogenic factors exhibited in preeclampsia is a major component of its pathophysiology. In this regard, measurement of circulating levels of soluble tyrosine kinase-1 similar to fms (sFlt-1), a decoy receptor for vascular endothelial growth factor (VEGF), is a moderately reliable biomarker for the diagnosis of preeclampsia. However, few studies have established a mechanistic approach to determine how the high levels of sFlt-1 are responsible for the endothelial dysfunction, and even less is known about its effects at the blood-brain barrier (BBB). Since the expression pattern of VEGF receptors type 1 and 2 in brain endothelial cells differs from the observed in peripheral endothelial cells. Plus, components of the neurovascular unit of the BBB provide paracrine secretion of VEGF. This compartmentalization of VEGF signaling could help to see in a different viewpoint the role of sFlt-1 in the development of endothelial dysfunction. In this article, we provide a hypothesis of how sFlt-1 could eventually be a protective factor for brain endothelial cells of the BBB under preeclampsia.